En marge des institutions ? - Lucille Lisack (Revue d'anthropologie des connaissances)
Basing on the ethnography of institutions considered as processes and not as static objects, this article analyses the institutionalization of the musical category “contemporary music” in Uzbekistan in the 1990s and 2000s. The period corresponds to the profound institutional changes following the collapse of the USSR. The observation focuses on two events which occasioned practices and discourses that gave a new shape to the musical landscape of Tashkent: an “international festival of contemporary music” and a master class for young composers. These two events were first supported only by NGOs and occurred outside of state institutions, but then the organisers got closer to the state musical institutions. Analysing the insertion of the category “contemporary music” in the institutional system of the country, this article shows how institutions and instituted categories shape one another.